A 'striking' relationship: scorpion defensive behaviour and its relation to morphology and performance. (3rd April 2017) - Coelho, Pedro; Kaliontzopoulou, Antigoni; Rasko, Mykola; van der Meijden, Arie
Summary: Like many other venomous organisms, scorpions use their venom in defence against predators. Scorpions apply their venomous stinger by extending the caudal part of the body, the metasoma, forward towards the attacker. There are considerable differences in metasoma morphology among scorpion species, and these may afford differences in defensive strike performance. We investigated the movement trajectory and kinematics of the defensive strike in seven species of scorpions, and how these variables are related to each other, and to morphology. We recorded defensive strikes using high‐speed video, and reconstructed the trajectory of the telson. From these trajectories, we calculated velocity, acceleration and other kinematic variables. To compare strike trajectory shapes, we used geometric morphometrics. We have shown that the defensive strike differs in trajectory shape, speed, path length and duration between scorpion species. Body size is also an important factor affecting strike characteristics. Relative metasoma length and girth may also influence strike performance, as well as strike trajectory shape. Strikes with different trajectories have different kinematic properties: those with open trajectory shapes attain higher speeds. Our results show that performance differences in defensive behaviour between different scorpion species may be partly mediated by morphology, binding together phenotypic, functional and behavioural diversity. A lay summary is available for this article. Abstract : Lay Summary